Post-stroke health-related quality of life at 3 and 12 months and predictors of change in a Danish and Arctic Norwegian Region - Heiberg, Guri Anita; Friborg, Oddgeir; Pedersen, Synne Garder; Thrane, Gyrd; Stabell, Henriette Holm; Nielsen, Jørgen Feldbæk; Anke, Audny (Journal of Rehabilitation Medicine, 2020)
Objectives: To investigate changes in health-related quality of life between 3- and 12-months post-stroke in a north Norwegian and a Danish region that organize their rehabilitation services differently, and to identify clinically relevant predictors of change. Design: Prospective multicentre cohort study. Subjects: In total, 304 patients with first-ever stroke (male sex 59%, mean age 68.7 years) participated from Norway (n = 170) and Denmark (n = 134). Methods: The Quality of Life after Brain Injury-Overall Scale (QOLIBRI-OS) was administered twice to measure change in satisfaction with function and wellbeing. Results: QOLIBRI-OS scores showed a small statistically significant difference in favour of Norway at 12 months post-stroke (p = 0.02; Cohen’s d = 0.26). Using a calculated minimal clinically important difference score of 12, 20% reported worse, 54% unchanged and 26% better QOLIBRI-OS scores between 3 and 12 months. Age below 65 years predicted a negative change (odds ratio (OR) 0.4, p = 0.007). Conclusion: In this population with mild and moderate stroke, QOLIBRI-OS scores were slightly higher in the Norwegian region. Approximately 50% of participants experienced clinically important changes in satisfaction with functioning and wellbeing between 3 and 12 months post-stroke. Younger age predicted negative change. This result could indicate increased rehabilitation needs over time in young patients and should be investigated further.